Cash Recording Information System For Receipts and Expenditures: Study At One Of The Schools In Bandung - Windy Wiandiny Wulandari; Ramlan Ramlan; Ganjar Nurul Fajar; Isbandi Isbandi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study aims to develop and execute a web-based cash receipt and disbursement information system to address financial management issues in a school in Bandung. Before the system's development, cash transaction recording was conducted manually with notebooks and spreadsheets, susceptible to inaccuracies, reporting delays, and inefficiencies in time and effort. An information system was built to address these issues by streamlining transaction recording, accelerating the reporting process, and enhancing the accuracy and efficiency of cash management. This study employs data-gathering methods such as interviews, observations, literature reviews, and documentation analysis. The system was developed utilizing a prototyping methodology, facilitating extensive contact between engineers and users to create a solution that meets their requirements. This system was constructed utilizing the PHP programming language alongside the Laravel framework, employing a MySQL database operated via XAMPP and written with the Visual Studio Code editor. The findings of this study demonstrate that the developed cash receipt and disbursement information system can enhance schools' ability to record and manage cash transactions with greater efficiency, accuracy, and organization. This technology facilitates the generation of rapid cash reports that are accessible at any time, thereby enhancing the decision-making process and ensuring transparent financial reporting. Consequently, this system serves as an appropriate solution for facilitating the digitalization of financial administration within the educational setting.